2015
DOI: 10.1002/pola.27994
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-made and chemically designed synthesis of coumarin-containing benzoxazines and their reactivity study toward their thermosets

Abstract: Coumarins are used as a natural renewable resource to synthesize coumarin-containing benzoxazine resins. The coumarin-containing benzoxazines are fully characterized in terms of their chemical structure by Fourier-transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. The influence of electronic effects caused by the substituents on the polymerization temperature is also evaluated. Thermal properties of the resulting thermosets are characterized by differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…The neat PUs showed typical glass transition temperature, T g , values of PCL in the range –55 °C to –45 °C and the T m at around 40–50 °C . The T g values increased with CD amount for all PU formulations, due to CD increasing the steric restriction toward molecular rearrangements and thus impairing polymer chain mobility, which leads to a higher value of T g . PU530s exhibited their melting transitions at lower temperatures than their PU2000s counterparts due to their shorter chains and smaller PCL crystal sizes…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The neat PUs showed typical glass transition temperature, T g , values of PCL in the range –55 °C to –45 °C and the T m at around 40–50 °C . The T g values increased with CD amount for all PU formulations, due to CD increasing the steric restriction toward molecular rearrangements and thus impairing polymer chain mobility, which leads to a higher value of T g . PU530s exhibited their melting transitions at lower temperatures than their PU2000s counterparts due to their shorter chains and smaller PCL crystal sizes…”
Section: Resultsmentioning
confidence: 96%
“…[40] The T g values increased with CD amount for all PU formulations, due to CD increasing the steric restriction toward molecular rearrangements and thus impairing polymer chain mobility, which leads to a higher value of T g . [7] PU530s exhibited their melting transitions at lower temperatures than their PU2000s counterparts due to their shorter chains and smaller PCL crystal sizes. [41] The introduction of CD did not significantly modify T m values of PU530s but it considerably reduced the crystallinity, shown by a decrease in the melting enthalpy (Table 2).…”
Section: Differential Scanning Calorimetrymentioning
confidence: 98%
See 1 more Smart Citation
“…[15] Up to now,alarge quantity of biobased benzoxazines have already been prepared from the renewable cardanol, [16,17] diphenolic acid, [18,19] phloretic acid, [20] furfurylamine, [21,22] stearylamine, [23] coumarin, [24,25] umbelliferone, [26] and more recently the lignin derivatives (guaiacol, [27][28][29][30] vanillin, [31][32][33] and eugenol [34][35][36][37][38] ). [15] Up to now,alarge quantity of biobased benzoxazines have already been prepared from the renewable cardanol, [16,17] diphenolic acid, [18,19] phloretic acid, [20] furfurylamine, [21,22] stearylamine, [23] coumarin, [24,25] umbelliferone, [26] and more recently the lignin derivatives (guaiacol, [27][28][29][30] vanillin, [31][32][33] and eugenol [34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…For instance, arbutin, furfurylamine, and paraformaldehyde were used to synthesize a water‐soluble benzoxazine by Dubois . Coumarin was used to synthesize a series of bio‐based benzoxazines by Ishida, who found that monomers based on coumarin are photopolymerizable and that the surfaces of corresponding polymers have good hydrophobicity . Cádiz synthesized a series of tough benzoxazine resins using castor oil, and eugenol was used to synthesize a series of bio‐based benzoxazines and composite materials by Thirukumaran et al .…”
Section: Introductionmentioning
confidence: 99%